2005
DOI: 10.1016/j.atmosenv.2004.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal changes in the distribution of dicarboxylic acids, ketocarboxylic acids and dicarbonyls in the urban Tokyo atmosphere

Abstract: Secondary organic aerosol in the urban atmosphere is an important issue from a viewpoint of not only air pollution but also regional and global atmospheric environment. To better understand the production of water-soluble organic aerosols, we analyzed atmospheric particles collected in time-series in Tokyo for dicarboxylic acids (C2-C10), ketocarboxylic acids (C2-C4) and a-dicarbonyls (C2-C3) using a GC and GC/MS. Here, we report, for the first time, diurnal distributions of dicarboxylic acids, ketoacids and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
310
14

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 340 publications
(351 citation statements)
references
References 38 publications
27
310
14
Order By: Relevance
“…Thus C 6 /C 9 ratio has been utilized as a tracer to estimate the anthropogenic v.s. biogenic contributions to organic aerosols (Kawamura and Yasui, 2005). In the present study, C 6 /C 9 ratios present greater values during daytime (0.5-2.0, av.…”
Section: Diurnal Variations Of Dicarboxylic Acids Oxocarboxylic Acidcontrasting
confidence: 42%
See 3 more Smart Citations
“…Thus C 6 /C 9 ratio has been utilized as a tracer to estimate the anthropogenic v.s. biogenic contributions to organic aerosols (Kawamura and Yasui, 2005). In the present study, C 6 /C 9 ratios present greater values during daytime (0.5-2.0, av.…”
Section: Diurnal Variations Of Dicarboxylic Acids Oxocarboxylic Acidcontrasting
confidence: 42%
“…Generally, TC concentrations and their proportions in aerosol mass should be controlled by emission strengths, photochemical processing and/or dilution by inorganic species. TC values and their proportions to aerosol masses in Mangshan are smaller than those (49 µg m -3 , 17%) reported from Beijing (Sekine et al, 1992) and those (24 µg m -3 , 21%) from Tokyo (Kawamura and Yasui, 2005), but are significantly greater than those (0.38 µg m -3 , 0.75%) reported in the remote marine aerosols from the Pacific (Kawamura and Sakaguchi, 1999), in which sea-salts are abundant.…”
Section: Concentrations Of Tsp Mass and Total Carbonmentioning
confidence: 54%
See 2 more Smart Citations
“…Kawamura (1979) and Mikami (2003) showed that the increasing rate of T min was greater than that of T max from the data at the Tokyo observatory from 1876 to 1970 and from 1900 to 2000, respectively, thus indicating a decrease in DTR by the effects of urbanization. Kondo (2009) estimated the effects of urbanization on temperature by using a simple one-dimensional boundary layer model.…”
Section: Introductionmentioning
confidence: 99%